2014
DOI: 10.2478/orhu-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Preference of Great-Spotted Woodpecker (Dendrocopos major Linnaeus, 1758) and Lesser-Spotted Woodpecker (Dendrocopos minor Linnaeus, 1758) in the Presence of Invasive Plant Species - Preliminary Study

Abstract: Gábor Ónodi & Tibor Csörgő 2014. Habitat preference of Great-spotted Woodpecker (Dendrocopos major Linnaeus, 1758) and Lesser-spotted Woodpecker (Dendrocopos minor Linnaeus, 1758) in the presence of invasive plant species -preliminary study. -Ornis Hungarica 22 (2): 50-64. AbstractThis study was carried out in Hungary, in an old, unmanaged, riparian poplar-willow forest, where two invasive tree species, the green ash and the boxelder maple are presented and reproduce more effectively therefore are more abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Among native trees, nest site plots had more trees from all of the available three species, but the difference was proportionately bigger in terms of willow and black poplar hybrid trees, than white poplar hybrids. In one of our earlier studies made in the same study area, through weekly standard, year-round foraging observations, we found, that invasive tree species were avoided (Ónodi & Csörgő 2014). In spite of that, among other tree species, the rough barked native willow and black poplar hybrids were the most preferred trees for foraging (Ónodi & Csörgő 2014).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Among native trees, nest site plots had more trees from all of the available three species, but the difference was proportionately bigger in terms of willow and black poplar hybrid trees, than white poplar hybrids. In one of our earlier studies made in the same study area, through weekly standard, year-round foraging observations, we found, that invasive tree species were avoided (Ónodi & Csörgő 2014). In spite of that, among other tree species, the rough barked native willow and black poplar hybrids were the most preferred trees for foraging (Ónodi & Csörgő 2014).…”
Section: Discussionmentioning
confidence: 67%
“…In one of our earlier studies made in the same study area, through weekly standard, year-round foraging observations, we found, that invasive tree species were avoided (Ónodi & Csörgő 2014). In spite of that, among other tree species, the rough barked native willow and black poplar hybrids were the most preferred trees for foraging (Ónodi & Csörgő 2014). The green ash and boxelder maple were scarcely used for foraging by the study species (Ónodi & Csörgő 2014).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations